Partner Violence During Pregnancy and its Affecting Factors a Province in Eastern Turkey - Celebi, E.; Pirincci, E.; Durmus, A. B. (Wolters Kluwer Medknow Publications, 2020)
Background: The violence experienced by a woman during her pregnancy period has a direct impact on both mother and child, and it generally harms the development of the family and society. Aim: This study was conducted to determine spouse violence experiences of married women aged 15 years and older during their pregnancy period who live in a province in eastern Turkey. Materials and Methods: This descriptive study was carried out with 712 married women living in a city center in Turkey. Participants were selected by systematic sampling from the records by reaching to all family health centers in the city. The field study was conducted between April and June 2015. The questionnaire was prepared by the researchers. The findings of the study were evaluated in SPAS version 22 software package. Chi-square test and multidimensional logistic regression analysis were used in the analysis. P < 0.05 was considered statistically significant in the comparisons. Results: In our study, having a kinship relationship with her husband, lack of education of herself and her husband, and lack of employment by the woman were found to be the risk factors for violence during pregnancy period (P < 0.05). The fact that she was exposed to physical violence from her husband during her no pregnancy period, and that the woman was beaten by her father during her childhood period increased the risk of violence during pregnancy period (P < 0.05). Conclusion: The rate of exposure to physical violence by her spouse during pregnancy period is high. The provision of education and employment can increase a woman's social networks and improve her status within the family.
Keywords: Pregnancy; Turkey; violence; women